On the use of the locative adverbs bura-, ora- and şura- in Turkish - Butkevičiūtė, Beata (Taikomoji kalbotyra, 2015)
The paper deals with the Turkish deictic locative adverbs bura- (‘here’) ora- (‘there’) and şura- (‘here’, ‘there’). Some researchers (Lyons 1977, Levinson 1983, Anderson and Keenan 1985) claim that şura- occupies an intermediate position between bura- and ora-. Some others (Küntay and Özyürek 2002, 2006) note that şura- is neutral with regard to distance specifications. This investigation has identified a rather problematic usage of the deictic locative adverb şura-. Taking into account that contemporary Turkish language has gradually developed from a three-member deictic system into a two-member system, the paper attempts to more thoroughly investigate the usage of the locative adverb şura- and describe the prevailing deictic system in the Turkish language.